The systematic development of guidance for parents on talking to children of primary school age about weight - Fiona B. Gillison; Elisabeth B. Grey; Fran Baber; Angel Chater; Lou Atkinson; Alison Gahagan (BMC, 2023)
Abstract Background The prevalence of overweight and obesity in children is increasing, alongside increases in rates of children's anxiety and worry about their weight. In many countries children's weight is measured, and parents are made aware if a child has been classified as having overweight or obesity. However, many parents are concerned that raising their child's awareness of their weight, and talking to children about their weight could harm their wellbeing. The aim of this project was to develop guidance for parents on constructive ways to talk to children of primary school age about weight when they need to. Methods The project followed a mixed-methods design: Phase 1 involved the collation of evidence including (a) two previously published systematic literature reviews to identify the associations between parent-child weight talk, and broader health discussions, and children's wellbeing, (b) interviews with children, and (c) development and refinement of narrative messaging (previously published). In Phase 2 we developed a conceptual model and mapped primary findings to techniques and content within a draft guidance document for parents on talking to children about weight. Phase 3 involved a modified Delphi process with 29 stakeholders to refine and agree a final version. Results An acceptable draft guidance was agreed following two stages of feedback from Delphi participants. Key areas for debate and adaptation included: encouraging discussion about health and growth with lesser focus on weight; finding ways to reduce stigma and perceptions of blame; emphasising a whole-family approach; inclusive representation of diversity among children and families. Conclusions Consensus on the content of guidance for parents on talking to children about weight was achieved through a process of evidence review and stakeholder and expert engagement. The next steps are to measure the impact of the resource on improving the experience of parents and children in communicating about weight.